The Adoption of Blockchain In Supply Chain: Is Supply Chain Ready? - Emy Ezura A-Jalil (International Journal of Supply Chain Management, 2020)
Recently, blockchain technology is getting its recognition in the supply chain. After the existence of bitcoin, which blockchain acts as its underlying technology, people started to recognise the advantages of the blockchain. Blockchain has been expected to eliminate unnecessary cost and at the same time, help in improving productivity by increasing the efficiency and effectiveness in daily operation. In the era of Industrial 4.0, the collaboration of blockchain technology with other autonomous technology is necessary to achieve customer satisfaction. However, based on the current practices, blockchain is yet to be adopted by all the parties in the supply chain. Therefore, this paper aims to identify the factors which are affecting the adoption of blockchain technology in the supply chain. Factors identified are perceived benefits, top management support and supply chain partner readiness. The primary data has been collected through a structured questionnaire survey. The simple random sampling method has been used to target and collect data from suitable respondents. In conclusion, the outcome of this study is expected to identify the factors affecting the adoption of the blockchain as well as to guide the organisation to act according to increase the level of adoption.